1999
DOI: 10.1136/tc.8.2.161
|View full text |Cite
|
Sign up to set email alerts
|

Development of smoking by birth cohort in the adult population in eastern Finland 1972-97

Abstract: Objective-To analyse the dynamics of smoking prevalence, initiation, and cessation in relation to sex, age, birth cohort, study year, and educational level. Results-Among men the prevalence of smoking decreased over time, but the cohort eVect observed in smoking initiation was obscured by the changes in smoking cessation. DiVerences between the educational categories were small. Among women the prevalence of smoking increased during the study period. This was mainly caused by the less highly educated, in whom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
40
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 25 publications
6
40
0
1
Order By: Relevance
“…This is consistent with Lopez and colleagues cigarette epidemic model, in which from stage II to stage III, male smoking prevalence first increases then declines, but female smoking prevalence keeps rising until reaching a plateau. Similar trends were found in population-based epidemiological surveys of smoking in Finland and Australia (Laaksonen et al, 1999;White et al, 2003). The Smoking and Health Survey in Australia reported that smoking prevalence in males was 40% in 1980 and only 25% in 2001, while female smoking prevalence was 30% in 1980 and 21% in 2001 (Laaksonen et al, 1999;White et al, 2003).…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…This is consistent with Lopez and colleagues cigarette epidemic model, in which from stage II to stage III, male smoking prevalence first increases then declines, but female smoking prevalence keeps rising until reaching a plateau. Similar trends were found in population-based epidemiological surveys of smoking in Finland and Australia (Laaksonen et al, 1999;White et al, 2003). The Smoking and Health Survey in Australia reported that smoking prevalence in males was 40% in 1980 and only 25% in 2001, while female smoking prevalence was 30% in 1980 and 21% in 2001 (Laaksonen et al, 1999;White et al, 2003).…”
Section: Discussionsupporting
confidence: 58%
“…Similar trends were found in population-based epidemiological surveys of smoking in Finland and Australia (Laaksonen et al, 1999;White et al, 2003). The Smoking and Health Survey in Australia reported that smoking prevalence in males was 40% in 1980 and only 25% in 2001, while female smoking prevalence was 30% in 1980 and 21% in 2001 (Laaksonen et al, 1999;White et al, 2003). If stratified by age, this secular trend still holds.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…In addition to current smoking status and consumption intensity, many surveys routinely collect retrospective information on age at smoking initiation as well as former smoking status and age at (or time elapsed since) smoking cessation. We follow the substantial literature which uses such retrospective smoking data to reconstruct smoking prevalence rates and analyse smoking patterns (i) across the life-course and over successive cohorts (Kemm, 2001;Kenkel, Lillard, & Liu, 2009;Kenkel, Lillard, & Mathios, 2003b;Laaksonen et al, 1999;Lillard & Christopoulou, 2015), and (ii) with respect to educational gradients (Christopoulou, Lillard, & de la Miyar, 2013;Federico, Costa, & Kunst, 2007;Pampel, 2005;Pampel et al, 2015).…”
Section: The Life-course Approachmentioning
confidence: 99%